Predictors of suicidal ideation in middle school students in the Dominican Republic - Sancho, Patricia; Suero-Maloney, Carlos Manuel; Tomás, José Manuel; Córdoba, Ana Isabel; Jiménez-Hernández, David; Esnaola, Igor (Pensando Psicología, 2025)
Currently, suicide has become the second cause of death among adolescents, with some attempts occurring in middle schools. Cases of suicide attempts are becoming increasingly worrisome. In this research, a model for predicting suicide ideations associated with different variables was tested on 531 adolescents from the Dominican Republic to contribute to its understanding. Statistical analyses included Confirmatory Factor Analyses (CFAs) to test psychometric properties of the constructs of interest, and Structural Equation Models (SEMs) to test for the effects among the constructs. The results displayed the predictive power of factors as being bullied, emotional instability and prosocial behaviour on verbal and physical aggressiveness and self-esteem and, in turn, how these effects predict suicidal ideation. These results contribute to the understanding of the role bullying has on adolescent’s suicidal tendencies and the mediated paths for this effect, which may guide the design for future prevention programs.